1999
DOI: 10.1007/s004250050587
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of a cDNA encoding a starch synthase from potato ( Solanum tuberosum L.) that is predominantly expressed in leaf tissue

Abstract: Three isoforms of starch synthase (SS) were shown to be present in soluble potato tuber extracts by activity staining after native gel electrophoresis. A cDNA encoding SSI from rice was used as a probe to clone a corresponding cDNA from potato. The deduced amino acid sequence identified the protein as an SS from potato with an M(r) of 70.6 kDa for the immature enzyme including its transit peptide. This novel isoform was designated SSI. An analysis of the expression pattern of the gene indicated that SSI is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…Accordingly, the modification of the starch structure by antisense repression of starch synthases or branching enzymes significantly affect the starch phosphate content (20)(21)(22)(23). The actual target structure(s) that are recognized by R1 as a phosphorylation site(s) remain(s) to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the modification of the starch structure by antisense repression of starch synthases or branching enzymes significantly affect the starch phosphate content (20)(21)(22)(23). The actual target structure(s) that are recognized by R1 as a phosphorylation site(s) remain(s) to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complete absence of SSI has no effect on the size and shape of seeds and starch granules or the crystallinity of endosperm starch, suggesting that other SS isoforms are capable of partly compensating for the absence of SSI function [51]. Kossmann et al [104] reported that the reduction of potato SSI in antisense plants did not lead to detectable changes in starch structure. They suggested that this lack of change was because potato SSI was predominantly expressed in leaves and only represented a minor activity in potato tubers, where SSII and SSIII were the major isoforms expressed.…”
Section: Soluble Starch Synthasementioning
confidence: 99%
“…Kossmann et al (1999) reported that the reduction of potato SSI in antisense plants did not lead to any detectable changes in starch structure in the tuber, since in potato SSI is predominantly expressed in leaves and only to a lower extent in the tuber where SSII and SSIII are the major isozymes expressed. In Arabidopsis mutants defective in SSI (Delvalle et al, 2005), which is one of the major isozymes in its leaves, the chain-length distribution of amylopectin showed a decrease in DP 8 to 12 branches and an increase in DP 17 to 20 branches.…”
mentioning
confidence: 99%